Implementation Of Communication In Improving The Quality Of Education - Agus Suryadi (AT-TAKILLAH : Jurnal Pendidikan dan Keislaman, 2023)
The study of the article that will be discussed by the author is about how the implementation of communication between the head of the madrasa in improving the quality of education, what communication is built by the head of the madrasa with teachers, staff and madrasa committees, and the forms of communication that are built by the head of the madrasa with teachers, staff madrasa leaders and committees. The purposes of this article are: 1) to find out the implementation of Communication in Islamic Perspective, 2) to know the Definition of Organization and Organizational Communication 3). to find out the implementation of communication between the Head of Madrasah and teachers in improving the quality of education. This article was conducted using a library study approach. Literature study is a data collection technique by conducting a review study of books, literatures, notes, and reports that have to do with the problem being solved. The results of the article show that the Madrasah Principal must carry out communication with teachers, staff and madrasa committees to improve the quality of education.